Digitalization Capability and Organizational Performance: The Mediating Role of Organizational Agility - Heri Soesanto; Dwi Wulandari; Thomas Soseco (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
Digitalization is prominent for companies and businesses, especially in the era of modern information technology. Digitalization can increase efficiency in business processes, including manufacturing, supply chains, inventory management, and administrative processes. Hence, this study aims at investigating the role of organizational agility in mediating the relationship between digitalization capability and business performance. A purposive sampling was used to gather the data from managers in PT. Mayora Indah Tbk. Furthermore, the data were analyzed using structural equation modeling. The findings indicate that digitalization capability has a significant effect on organizational performance and organizational agility. In addition, this study showed that digitalization capability has an effect on organizational agility. This study also confirms the role of organizational agility in mediating the link between digitalization capability and organizational performance. This study provides implications for the need for organizational agility in supporting digitalization capability and organizational performance. Keywords: organizational performance, organizational agility, digitalization capability